The Promotion of the Zero-Waste Concept by Influencers in Social Media - Buczyńska-Pizoń, Natalia (Journal of Public Governance, 2021)
Objectives: The aim of the conducted research was to examine the level of knowledge of the idea of zero waste as well as to correlate it with the use of social media and influencers’ followings.Research Design & Methods: The research methods used in the study are as follows: descriptive research, Internet research, observation, and graphical presentation of data.Findings: Those respondents who see that influencers promote the zero-waste concept have significantly higher index of the time spent in social media. Education level of the survey participants does not translate into the level of knowledge about the zero-waste concept.Implications / Recommendations: The analysis shows that values of the promotion of the zero-waste concept are important in caring about the natural environment. Influencers can effectively promote the zero-waste concept via social media.Contribution / Value Added: The author tries to show the purpose of the promotion of the said concept by using influencers in social media. The topic of environmental care is extremely important, especially in this day and age, when the climate crisis is progressing. Influencers who impact their customers can contribute to the spread of the zerowaste concept, which fits into an alternative economic model – namely circular economy – in place of a linear model.Article classification: research articleJEL classification: M31, Q51, Q54